2011
DOI: 10.1177/0020764010390439
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of people with mental illness who are under treatment in traditional healer centres in Sudan

Abstract: This study improves the understanding about what types of people with mental illness are treated at these traditional healer centres and gives recommendations that can help in improving the quality of services in these centres. It can probably be used in building bridges of collaboration between these centres and the available mental health and psychiatric services in Sudan, especially at primary healthcare level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 15 publications
1
31
1
Order By: Relevance
“…132 In Sudan, more than one-third (41%) of patients with mental disorders had sought the service of a TCAM practitioner prior to accessing conventional care. 130 Musculoskeletal conditions A total of seven (six Nigerian, one Ghanaian) studies drawn from small samples reported TCAM product and practitioner use for musculoskeletal conditions. Two studies reported 96.8% of peasant farmers 41 and 40.2% of occupational drivers 133 as using TCAM products for the management of musculoskeletal pain.…”
Section: Malaria and Febrile Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…132 In Sudan, more than one-third (41%) of patients with mental disorders had sought the service of a TCAM practitioner prior to accessing conventional care. 130 Musculoskeletal conditions A total of seven (six Nigerian, one Ghanaian) studies drawn from small samples reported TCAM product and practitioner use for musculoskeletal conditions. Two studies reported 96.8% of peasant farmers 41 and 40.2% of occupational drivers 133 as using TCAM products for the management of musculoskeletal pain.…”
Section: Malaria and Febrile Illnessmentioning
confidence: 99%
“…129 Another study from Sudan reported that mental health patients who visit traditional healers were men, with an average age of 31 years, illiterate or with only a primary education, and unemployed. 130 TCAM users among students, healthcare professionals, academic staff and general outpatient population A Ghanaian study observed that TCAM users were more likely to be Christians enrolled in non-science-related programmes at the university. 35 In Sierra Leone, healthcare students' gender, age and year of study were not associated with TCAM use, 36 37 although being a Christian was associated with the use of spirituality/prayer among pharmacy students.…”
Section: Tcam Users Seeking Infertility Carementioning
confidence: 99%
See 1 more Smart Citation
“…Explanatory models (EM) is a term introduced by Kleinman, referring to “notions about an episode of sickness and its treatment that are employed by all engaged in the clinical process” [20]. Recent studies in Africa on EM—concerning various common mental disorders such as psychosis [21-24], epilepsy [25], depression [26], or mental illness in general [27-30]—illustrate a wide range of locally used categories and explanations for Western categories of mental illness. It is also acknowledged that traditional healers play an important role in dealing with distress, especially in countries where Western psychological services are extremely limited [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The patients are deprived of all types of food apart from a special porridge made in the centre. All medications are stopped except those provided by the traditional healers and their assisting therapists (Sorketti & Habil, 2009). Ahmed, Bremer, Magzoub and Nouri (1999) investigated the characteristics of visitors to traditional healers in Sudan in a sample of 134 visitors at four centres.…”
Section: Introductionmentioning
confidence: 99%